New species and new geographical records in Ecuadorian Lamiinae (Coleoptera, Cerambycidae) - Vlasak, Josef; Santos-Silva, Antonio (Zootaxa, 2022)
Three new species of Lamiinae are described from Ecuador: Pseudosparna pallida sp. nov. (Acanthocinini); Acakyra sinuata sp. nov. and Scythropopsis variegata sp. nov. (Acanthoderini). Piriana pygmaea (Bates, 1881) is recorded from Ecuador for the first time. A chromatic variation in Unaporanga lanceolata Martins & Galileo, 2007 is reported, the male is illustrated for the first time, and the species is newly reported from the Ecuadorian department of Pichincha. The morphological differences between Scythropopsis Thomson, 1864, Acakyra Martins & Galileo, 1996, and Irundisaua Martins & Galileo, 2005 are discussed.